Skull osteology of aetosauroides scagliai casamiquela, 1960 (archosauria: Aetosauria) from the late triassic of Brazil: New insights into the paleobiology of aetosaurs - Neto, Voltaire Dutra Paes (2021)
Aetosauroides scagliai, from the Ischigualasto Formation of Argentina and Santa Maria Supersequence of Brazil (Carnian-Norian), is one of the oldest members of Aetosauria, a diverse clade of armored crocodile-line archosaurs. Aetosauroides scagliai differs from other aetosaurs in having the maxilla excluded from the margin of the external nares, the length/width ratio of the postzygapophyses ≤ 0.75, and other features that place it as one of the earliest-diverging members of the clade. In this paper we provide a detailed description of the skull of A. scagliai based on a new Brazilian specimen, revealing that it lacks a pneumatic cavity on the medial surface of the maxilla and further differs from all other known aetosaurs by the presence of ≥ 12 dentary teeth. However, contra previous studies, the elongated posterior process of the jugal does articulate ventrally with the quadratojugal in A. scagliai, forming the posteroventral corner of the skull as in all other aetosaurs. Aetosauroides scagliai exhibits some characters typical of predatory archosaurs (like the recurved ziphodont teeth and mandibular articulation at the level of the tooth row), but was probably an omnivore, as it also shares several probable adaptations for herbivory with aetosaurs generally (i.e., edentulous anterior premaxilla and dentary) and stagonolepidoids specifically (e.g., shovel-shaped snout). This suggests that there was greater trophic diversity in this clade than usually recognized, at least early in their evolutionary history.